E – Hrm “Electronic Human Resource Management” – Its Effectiveness In Hotels (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Human Resource is an important department in any organization. This department helps bridge the gap  between the organization expectation and the workforce who are working towards fulfilling the expectations. The success  of any organization lies in the hands of Human resources working for them. Globally the pace of work is handled effi ciently by the electronic medium available today. On the same lines Electronic Human Resource management (E-HRM )  was adopted in the hospitality industry. E- HRM is basically practicing administration with the help of technology. Objective: The study analyzed the effective coordination within the organization with E- HRM. Methodology: The  study adopted the descriptive research design. The target population of the study was 25 Human Resource professionals  of the 5-star hotels across India. Results: E-HRM helps in maintaining effective coordination within the department.  It acts like a platform to work coordinately within the department, as it is compatible to use (32%), helps in decision  making (36%), accessing the information etc. for the whole organization (52%). Conclusion: E- HRM played a great  role in ensuring that individuals and teams perform their tasks as required, it is shown that the application of electronic  human resources has a positive effect on raising the efficiency of companies, and this gives the human resources a great  importance.
Keywords: E- HRM; Human Resource; Efficiency; Performance